Preparation of baicalein from baicalin using a baicalin-β-D-glucuronidase from Aspergillus niger b.48 strain. (October 2020) - Yu, Hongshan; Han, Yuting; Liu, Chunying; Wu, Xuebin; Sun, Changkai; Xu, Longquan; Jin, Fengxie
Graphical abstract: Highlights: Baicalin-β-d -glucuronidase from Aspergillus niger b.48 strain was purified. Purified enzyme, M.W., 45 kDa; optimal temperature, 50 °C; optimal pH, 5.0. Pure enzyme hydrolyzed baicalin to baicalein, did not hydrolyze glycyrrhizin. 1% baicalin was reacted at pH 5.0 and 50 °C for 24 h into baicalein by crude enzyme. 10.7 g baicalein was obtained from 20 g baicalin, molar yield, 88.4 %. Abstract: Baicalin-β-d -glucuronidase was produced from a culture of Aspergillus niger b.48 strain using Scutellaria root extract as an enzyme inducer, purified and characterized. The enzyme's molecular weight was approximately 45 kDa; its optimal operating temperature and pH were 50 °C and 5.0, respectively. The enzyme specifically hydrolysed 7- O -β-d -glucuronide of baicalin into baicalein, weakly hydrolysed β-d -glucuronide of p -nitrophenyl-β-d -glucuronide and p -phenolphthalein-β-d -glucuronide, but did not hydrolyse β-d -glucuronide of glycyrrhizin. The Michaelis constant ( Km ) was 21.74 mM; Vmax was 11.63 mM/h. Common metallic ions almost did not effect enzyme activity; greater than 10 mM/L Cu 2+ and greater 50 mM/L Fe 3+ ion strongly inhibited enzyme activity. The use of pure enzyme in baicalin conversion to baicalein was costly, the crude baicalin-β-d -glucuronidase from A. niger b.48 strain was used in the preparation of baicalein from baicalin to keep costs low. The optimum conditions for baicalein production from crude enzyme reaction were 1% baicalin reacting for 20 h–24 h at pH 5.0 and 50 °C. Here, 10.7 g baicalein was obtained from 20 g baicalin using the crude enzyme, and the molar yield was 88.4 %. Therefore, active baicalein was successfully produced at low cost from baicalin using a non-transgenic crude enzyme from A. niger b.48.